ANALISIS USER EXPERIENCE DAN REDESIGN WEBSITE RSU PESANGGRAHAN DENGAN MENGGUNAKAN METODE USER CENTERED DESIGN (UCD) - Adam Dandy Putra Novianto (2021)
RSU Pesanggrahan is a Type D General Hospital in Pesanggrahan District which was previously a Puskesmas, Pesanggrahan District. Since 2002 until now the Pesanggrahan Hospital has experienced many changes and rapid progress. As the 4.0 industrial revolution progresses, the progress experienced by Pesanggrahan Hospital also includes the field of information technology such as the presence of information media in the form of websites. The website belonging to the Pesanggrahan Hospital has had a running system since 2015, also on the website of the Pesanggrahan Hospital it has many features such as a homepage, a profile of the Pesanggrahan Hospital, a practice schedule, a list of doctors, and so on. However, over time, it is necessary to assess the level of usability on the website. A high level of usability on a website is something that must be fulfilled in order for the website to achieve its original purpose. This study aims to improve the usability of the Pesanggrahan Hospital website system by applying the User Centered Design (UCD) method. The application of the UCD method is carried out by carrying out questionnaires, interviews, task modeling and prototyping which are also combined with measurements of the level of usability, namely effectiveness, efficiency, and satisfaction. In this study, the usability value increased by 52% and resulted in a redesigned form of the website which is expected to create effectiveness and efficiency in its use.